The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00266-015-0546-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the Cleft Profile by Patients with Cleft Lip and Palate, Cleft Surgeons, and Lay People

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Zhu et al (2016) included eleven articles in their recent systematic review about rating facial appearance of CLP patients: Five studies found that professionals were more critical than lay people, three studies found no significant difference, and three studies reported that lay people were more critical. Professionals might be more critical as they are trained to critically examine faces and notice fine differences in the degree of impairment, resulting in a more negative score (Eliason et al, 1991; Al-Omari et al, 2005; Meng et al, 2015). However, they also have a better appreciation of the results than do members of the public, as they are familiar with the whole range of possible outcomes in CLP patients (Eichenberger et al, 2014; Mosmuller et al, 2015; Stebel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al (2016) included eleven articles in their recent systematic review about rating facial appearance of CLP patients: Five studies found that professionals were more critical than lay people, three studies found no significant difference, and three studies reported that lay people were more critical. Professionals might be more critical as they are trained to critically examine faces and notice fine differences in the degree of impairment, resulting in a more negative score (Eliason et al, 1991; Al-Omari et al, 2005; Meng et al, 2015). However, they also have a better appreciation of the results than do members of the public, as they are familiar with the whole range of possible outcomes in CLP patients (Eichenberger et al, 2014; Mosmuller et al, 2015; Stebel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, they also have a better appreciation of the results than do members of the public, as they are familiar with the whole range of possible outcomes in CLP patients (Eichenberger et al, 2014; Mosmuller et al, 2015; Stebel et al, 2015). Lay people are rarely asked to assess an individual's attractiveness formally, only to rate the nasolabial area, resulting in more positive ratings, as they feel empathetic towards the CLP patient (Eliason et al, 1991; Meng et al, 2015). Similarly, many lay people are unfamiliar with CLP, and their own perception of the residual deformity may influence their assessment negatively (Stebel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Meng et al . 15 describe similar ratings between experts and lay raters. The Eurocleft project systematically applied an evaluation strategy based on the Likert scale to provide an extensive overview over the various treatment strategies available in Europe.…”
Section: Introductionmentioning
confidence: 97%
“…[24][25][26] This technique is also useful for obtaining cleft profiles of specific patient types. 27 Because patient photographs can now be uploaded to computers and analyzed using software, more delicate measurements can be performed by various observers. Different surgeons can evaluate the results according to their understanding of the anthropometric landmarks and draw conclusions about the surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%